Analyst Coverage and Corporate Tax Aggressiveness in Indonesia Stock Exchange - Wiwiek Prihandini (Bina Nusantara University, 2020)
This research aimed to examine the effects of analyst coverage on corporate tax aggressiveness in emerging markets that stock prices did not reflect available information in the capital market. The samples were 537 companies listed on the Indonesia Stock Exchange from 2015-2016. The samples were taken based on the criterion set by the researcher. The data were obtained from financial statements and fact books published by the Indonesia Stock Exchange. Abnormal Book-Tax Differences (ABTD) was used as a proxy of tax aggressiveness. Analyst coverage was measured by average income predicted from the year (t-1). The equation model showed the effects of analyst coverage on tax aggressiveness using the logistic regression. The findings show that, in a weak form of market, analyst coverage has a positive effect on tax aggressiveness. It means analyst coverage encourages management to carry out tax aggressiveness. The impact is that after-tax income becomes higher, it also results in higher earnings per share, but the tax burden paid to the government is decreased.